(untitled) (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This article will examine the private international law and substantive liability issues in proceedings against UK based parent companies for the actions of foreign subsidiaries. The UK Supreme Court’s landmark decision in Vedanta v Lungowe will be assessed.[1] Moreover, the post-Brexit implications for the viability of such claims before English courts will be considered. In the context of business-related civil claims for human rights violations, the European Parliament’s Committee on Legal Affairs has recently presented a draft proposal with recommendations to the Commission on corporate due diligence and corporate accountability.[2] These proposals include amendments to the European Union’s (‘EU’) Brussels Ia Regulation and the Rome II Regulation.[3] The author will introduce these new developments on jurisdiction and the applicable law in relation to corporate human rights abuse claims against EU based parent companies for the actions of foreign subsidiaries. [1] Vedanta Resources Plc and Another v. Lungowe and Others [2019] UKSC 20. (Lord Briggs with whom Lady Hale, Lord Wilson, Lord Hodge and Lady Black agreed) [2] See <https://www.europarl.europa.eu/doceo/document/JURI-PR-657191_EN.pdf> [3] See Council Regulation (EU) 1215/2012 of the European Parliament and of the Council of 12 December 2012 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters (recast) [2012] OJ L351/1 (‘Brussels Ia Regulation’); Regulation (EC) No 864/2007 of the European Parliament and of the Council on the Law Applicable to Non-Contractual Obligations [2007] OJ L199/40 (‘Rome II Regulation’).